Quality of turkeys breast meat affected by white striping myopathy - Carvalho, Larissa Tátero (2021)
The aim of this study was to characterize the breast meat of turkeys affected by different degrees of severity (normal [NORM], moderate [MOD], and severe [SEV]) of the white striping (WS) myopathy, as well as to evaluate the influence of this myopathy on meat quality. Twenty-nine samples of the pectoralis major muscles of each treatment were obtained from Nicholas breed male and female turkeys, reared and slaughtered in the center-west region of Brazil. The whole breasts of the turkeys were used for macroscopic classification, weight evaluation, and morphometric measurements. Then, the pectoralis major muscle was separated for histological evaluation and qualitative physicochemical analyses, namely ventral and dorsal color (L∗, a∗, and b∗), pH value, water holding capacity (WHC), cooking loss (CL), shear force (SF) (Meullenet-Owens Razor Shear [MORS] and Warner-Bratzler), sarcomere length, total, soluble, and insoluble collagen contents, proximate composition (protein, lipids, moisture, and ash), cholesterol content, and fatty acid profile. The results showed that muscles affected by myopathy, both MOD and SEV, exhibited larger weights (around 2.8 kg) compared to NORM muscles (1.3 kg) and a significant increase (P < 0.05) in the diameter of the fibers. The increase in the degree of severity of the myopathy increased (P < 0.05) the value of L∗ of the dorsal part and ventral part of the muscle. No differences (P > 0.05) were observed in the pH, CL, and WHC values of the muscles, whereas the MORS and Warner-Bratzler SF of the SEV fillets resulted in significantly lower shear values (P < 0.05) compared to the NORM fillets. In addition, the MOD and SEV fillets presented lower values of protein (P < 0.05) than NORM fillets. No significant differences (P > 0.05) were observed for moisture and lipid and cholesterol contents. Meat with MOD and SEV severity of WS myopathy had higher (P < 0.05) concentrations of total and insoluble collagen. Thus, the presence of WS myopathy in MOD and SEV degrees affected a large part of the histological and quality characteristics evaluated.